2018
DOI: 10.4172/neuropsychiatry.1000414
|View full text |Cite
|
Sign up to set email alerts
|

Resting-State Functional Connectivity within Default Mode Network in Chinese-speaking Children with Specific Learning Disabilities

Abstract: Learning is a complex process requiring support from various cognitive domains. Neuroimaging studies of clinical populations have linked various cognitive impairments with dysfunctions of the default mode network. This study investigates whether there is a fundamental deficit contributing to various sub-types of specific learning disability in children. Methods:Resting-state functional connectivity of the default mode network was examined using seedbased correlation and network-based statistical analyses. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 63 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…DMN is a large-scale network composed mainly of the posterior cingulate gyrus, precuneus, and medial prefrontal cortex. It has shown reduced connectivity in ASD patients compared with TD controls [46][47][48]. The dorsal attention network (DAN) is located in the intraparietal sulcus and frontal eye field.…”
Section: Resting-state (Rs-fmri)mentioning
confidence: 99%
“…DMN is a large-scale network composed mainly of the posterior cingulate gyrus, precuneus, and medial prefrontal cortex. It has shown reduced connectivity in ASD patients compared with TD controls [46][47][48]. The dorsal attention network (DAN) is located in the intraparietal sulcus and frontal eye field.…”
Section: Resting-state (Rs-fmri)mentioning
confidence: 99%
“…When looking specifically at networks typically defined by rs‐fMRI data sets, the default mode network (DMN) has shown hypoconnectivity 62,63 . Weng et al 65 used a seed in the posterior cingulate cortex to explore the DMN and found that 9/11 areas of the DNM showed reduced connectivity compared to adolescent controls. Decreased connectivity between the posterior cingulum and the right precentral gyrus (sensorimotor region) and right superior frontal gyrus within the DMN has also been implicated 66 .…”
Section: Functional Imagingmentioning
confidence: 99%